5G-NR Over Transparent Payload GEO Satellites: A Hands-On Approach Using OpenAirInterface5G-NTN - Sumit Kumar; Jevgenij Krivochiza; Turker Yilmaz; Jorge Querol; Symeon Chatzinotas; Stefano Andrenacci; Joel Grotz (IEEE Open Journal of the Communications Society)
The inclusion of Non-Terrestrial Network (NTN) components has significantly enhanced the reach of 5G networks. OpenAirInterface5G (OAI) has developed an open-source, Software-Defined Radio (SDR)-based framework for 5G-NTN, using its Terrestrial Network (TN) protocol stack as the baseline. OAI’s 5G-NTN adaptations are still evolving, requiring in-lab validations and field trials to assess its effectiveness in addressing the unique challenges of NTN components and channel characteristics. Live satellite tests, unlike simulations, demand manual tuning of key parameters like carrier frequency offset, timing offsets, and gain calibration. In this work, we present a practical approach for deploying 5G over GEO satellites using the OAI 5G-NTN suite, addressing (a) satellite channel impairments and (b) limitations in OAI’s current 5G-NTN implementation. Our work provides step-by-step calibrations, ensuring both experiment reproducibility and the realization of a full 5G-NTN link. We further identify the performance bottlenecks and experiment with (a) Radio Link Control Acknowledgment Mode (RLC-AM) parameters and (b) Low-Density Parity Check (LDPC) iterations to improve end-to-end throughput. We validate our methods via live tests over a transparent payload GEO satellite. We believe that our work represents a critical step in bridging the gap between lab-based 5G-NTN emulation and live satellite testing, offering valuable insights to advance 5G-NTN research and development.